Avaliação do uso e da estabilidade físico-química de misturas de herbicidas em tanque - (:unkn) unknown (Universidade Federal do Pampa, 2021)
Tank mixing is the use of two or more products in a spray tank, immediately before application. The aim of this work was to survey the use of pesticide mixtures in tanks and evaluate the physical compatibility of herbicide mixtures registered for irrigated rice (Oryza sativa L.) crops. The work was carried out in two stages, firstly a survey was carried out with professionals in the agronomic area through an online form; later an experiment was carried out under controlled conditions to test the physical compatibility of the main mixtures. The mixture preparation method for the physicochemical compatibility evaluation adopted was the one described in ABNT NBR 13875: Pesticides and other chemical products - Physicochemical compatibility evaluation, adopting the static technique, evaluating two volumes of spray mix, 100 and 25 L ha-¹. The evaluations were made immediately after mixing and at times 1, 5, 10, 30 minutes and 2, 6 and 24 hours after preparation of the mixture. The research carried out with professionals in the area can characterize the reality of the use of pesticide mixtures in tanks, mainly on the Western Border of Rio Grande do Sul. It was found that there is a large area and diversity of cultures where this practice is applied and that in these applications, most of up to four products are used per operation. The mixture of glyphosate + imazethapyr presents perfect stability at all times evaluated and in the two volumes of spray mix tested, being recommended for use without any restrictions. For the volume of 100 L ha-¹ the mixtures of glyphosate + clomazone and glyphosate + clomazone + imazapyr + imazapic are not recommended under these conditions. The same applies to the mixtures of glyphosate + clomazone, glyphosate + clomazone + imazapyr + imazapic, imazapyr + imazapic + bentazone, imazapyr + imazapic + quinclorac and imazapyr + imazapic + pyrazosulfuron-ethyl for the volume of 25 ha-¹. For the volume of 100 L ha-¹ the use of mixtures of imazapyr + imazapic + quinclorac, glyphosate + imazapyr + imazapic, imazapyr + imazapic + penoxsulam, imazapyr + imazapic + propanil + triclopyr, imazapyr + imazapic + fenoxaprop-p-ethyl, imazapyr + imazapic + imazethapyr and imazapyr + imazapic + bentazone is subject to a continuous stirring system so that incompatibility effects are minimized. The same applies for the volume of 25 L ha-¹ for the mixtures of imazapyr + imazapic + imazethapyr, imazapyr + imazapic + propanil + triclopyr, imazapyr + imazapic + fenoxaprop-p-ethyl and imazapyr + imazapic + cyhalofop butyl. Mixtures with the herbicides penoxsulam, quinchlorac and profoxydim have pH values lower than their pKa, showing that in these cases most of the herbicide molecules are in un-dissociated form.
Evaluation of the use and physical-chemical stability of herbicides mixtures in tank
Keywords: Arroz irrigado; Compatibilidade; Associação; Irrigated rice; Compatibility; Association; CNPQ::CIENCIAS AGRARIAS